1982
DOI: 10.1126/science.215.4531.353
|View full text |Cite
|
Sign up to set email alerts
|

Paleoflood Hydrology

Abstract: The difficult task of estimating recurrence intervals for large floods has long plagued hydrologists because statistical measures fail when return intervals of floods exceed the length of historical data sets. Sediments deposited in the backwaters of large floods may accumulate thick sequences in tributary mouths. Stratigraphic and sedimentologic studies of these sequences combined with radiocarbon dating have established a 10,000-year paleoflood record for the lower Pecos and Devils rivers in southwestern Tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(121 citation statements)
references
References 26 publications
1
118
0
2
Order By: Relevance
“…Sediments deposited by palaeofloods (Kochel and Baker, 1982) are of particular 45 interest because they can provide high resolution records of extreme hydrological 46 events occurring over short time periods, e.g. hours to days (Benito et al, 2004; 47 Baker, 2008).…”
mentioning
confidence: 99%
“…Sediments deposited by palaeofloods (Kochel and Baker, 1982) are of particular 45 interest because they can provide high resolution records of extreme hydrological 46 events occurring over short time periods, e.g. hours to days (Benito et al, 2004; 47 Baker, 2008).…”
mentioning
confidence: 99%
“…Ceci explique la netteté du contact entre le banc de graviers et la zone d'affouillement, de même que son évidente correspondance avec le prolongement de la rive intérieure du tributaire mineur. Il est également possible qu'un reflux sur le tributaire majeur ait causé le dépôt de sédiments immé-diatement en amont de la rencontre des écoulements (Kochel et Baker, 1982) et ait ainsi contribué à la surélévation du banc d'accumulation ( fig. 3b).…”
Section: Upstream View Of the Contact Between The Scour Hole And The unclassified
“…Floodplain sediments have been used extensively to reconstruct paleoflood frequency in a wide variety of physiographic and climatic settings (Brackenridge, 1981;1988;Kochel and Baker, 1982;1988;Baker et al, 1983;Ely and Baker, 1985), but only recently has the method been applied to ice-jam floods. Along the Yukon River Livingston et al (2009) showed that floodplain exposures containing repetitive overbank flood-deposited sediment layers separated by organic material can be used to reconstruct long-term ice-jam flood frequency.…”
Section: Methodsmentioning
confidence: 99%